Performance Improvement Strategy with Dynamic Capabilities in Service and Knowledge Management Aspects in PDAM Jember Regency - Ady Setiawan; Rini Rahmawati; Asrid Juniar; Ashari Sofyaun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the influence of resources on dynamic capabilities consisting of service and knowledge management aspects, as well as their effect on company performance at PDAM Kabupaten Jember. Resources are measured by indicators of production efficiency and distribution efficiency, service aspects are measured by indicators of technical services and consumer growth (customers), knowledge management is measured by indicators of the ratio of employees to consumers (customers), the ratio of education and training (training) employees, the ratio of training and education costs, company performance is measured by indicators of ROE, ROA, R and billing effectiveness. Research with SEM-PLS, research period 2011-2019, which is the period after all PDAMs in Indonesia carry out debt restructuring. The results of the study show that resources have a significant influence on aspects of service, knowledge management and company performance. Dynamic capabilities which consist of aspects of service and knowledge management have a significant influence on the company's performance of PDAM Kabupaten Jember. The results also show that dynamic capabilities are important for PDAM Kabupaten Jember to adapt to changes after debt restructuring.